Predictors of In-Hospital Mortality and Incomplete Kidney Recovery in Patients with Cirrhosis-Associated Non-Hepatorenal Syndrome Acute Kidney Injury: A Single-Center Retrospective Cohort Study - Daniela Rădulescu; Ileana Adela Văcăroiu; Andreea Manuela Franculescu-Bertea; Alex Nicolae Șendrescu; Alexandra Elisabeta Matea-Moldovan; Flavia Liliana Turcu; Daiana Cristina Brehui-Bertea (Journal of Clinical Medicine, 2026)
Background: Acute kidney injury (AKI) is associated with poor outcomes in patients with cirrhosis. However, most studies evaluate AKI as a single clinical entity, whereas predictors of mortality and renal recovery, specifically in non-hepatorenal syndrome AKI (non-HRS-AKI), remain poorly defined. Methods: We performed a retrospective cohort study including consecutive patients with liver cirrhosis admitted with non-HRS-AKI to a multidisciplinary emergency hospital between 1 January 2024 and 31 December 2025. Only variables available at hospital admission were included in the multivariable analyses. Independent predictors of in-hospital mortality and factors associated with incomplete renal recovery in survivors at hospital discharge were identified using multivariable logistic regression. Results: A total of 139 patients were included. Overall, 57 patients (41.0%) died during hospitalization. Among the 82 survivors, complete renal recovery occurred in 35 cases (42.7%), whereas 47 patients (57.3%) had incomplete renal recovery at discharge. Independent predictors of in-hospital mortality were a higher MELD-Na score (adjusted OR 1.16 per 1-point increase, 95% CI 1.07–1.26; p < 0.001), an advanced AKI stage (KDIGO stage 3 vs. stage 1, adjusted OR 6.71, 95% CI 1.73–26.04; p = 0.006), the absence of pre-existing chronic kidney disease (adjusted OR 0.233, 95% CI 0.085–0.644; p = 0.005), and higher admission C-reactive protein (adjusted OR 1.12 per 10 mg/L increase, 95% CI 1.01–1.23; p = 0.029). Factors independently associated with incomplete renal recovery among hospital survivors at hospital discharge were pre-existing heart failure (adjusted OR 3.07, 95% CI 1.10–8.62; p = 0.033) and higher admission C-reactive protein (adjusted OR 1.17 per 10 mg/L increase, 95% CI 1.00–1.34; p = 0.047). Conclusions: In patients with cirrhosis-associated non-HRS-AKI, in-hospital mortality was primarily associated with the severity of liver disease and AKI, whereas incomplete renal recovery at hospital discharge was independently associated with pre-existing heart failure. Admission C-reactive protein was independently associated with both outcomes, supporting the role of systemic inflammation in determining short-term prognosis and suggesting that C-reactive protein may serve as a simple, readily available biomarker for early risk stratification.